2003
DOI: 10.1021/jp022282q
|View full text |Cite
|
Sign up to set email alerts
|

Is the Anion the Major Parameter in the Shape Control of Nanocrystals?

Abstract: In this paper, copper nanocrystals are produced by using Cu(AOT)2−isooctane−water solution as a template. Even if the template does not change with various salt additions, the nanocrystal growth markedly depends on the salt used. It is demonstrated that chloride ions enable the growth of nanorods with an aspect ratio varying with chloride concentration. Conversely, only a slight amount of bromide ion is needed to increase the nanorod aspect ratio from 3 to 5 without any changes when increasing the bromide ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
179
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(203 citation statements)
references
References 49 publications
18
179
6
Order By: Relevance
“…4,14 Investigations have shown that the identity of anion species added as electrolyte are important for generating different shapes of copper nanocrystals. 56 The tendency is to follow the Hoffmeister series. 57 However, the initial micellar shape is shown to be largely unaffected by these additives.…”
Section: 4mentioning
confidence: 99%
“…4,14 Investigations have shown that the identity of anion species added as electrolyte are important for generating different shapes of copper nanocrystals. 56 The tendency is to follow the Hoffmeister series. 57 However, the initial micellar shape is shown to be largely unaffected by these additives.…”
Section: 4mentioning
confidence: 99%
“…Electrolytes: Some studies reveal the possible dependence of nanoparticle shape with electrolyte addition (Filankembo et al, 2003). Pileni (Pileni, 2003) has postulated that the selective ion or molecule adsorption over nanocrystal layers can affect their growth in certain directions, which could explain the apparent preference on certain particle shape.…”
Section: Surfactant and Cosurfactantmentioning
confidence: 99%
“…[30] It has also been found that addition of electrolytes has a great impact in controlling the nanocrystal shapes. [13,31] Indeed, halide ions interact with gold surfaces and the interaction strength follows the increasing order of F À < Cl À < Br À < I À . [31,32] Among the halides, F À ions nonspecifically adsorb to gold surface; Cl À ions also bind to gold through a weak interaction, whereas I À ions bind too strongly to gold surfaces and tend to destroy gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%